Mrs. pollifax on safari eaudiobook - Gilman, Dorothy (Mrs. Pollifax, 2018)
A safari expedition in Zambia is the disguise Emily employs in order to locate a professional assassin among her fellow explorers. Along the way, she meets an extraordinary man named Cyrus.